27.5k views
25 votes
Please show steps ASAP:

Simplify (6x^-2)^2(0.5x)^4.

Please show steps ASAP: Simplify (6x^-2)^2(0.5x)^4.-example-1
User Haplo
by
4.9k points

2 Answers

6 votes

Answer:


(9)/(2)

Explanation:


(6x^(-2))^2(0.5x)^4 =


= (6^2x^(-2 * 2)) ((1)/(2))^4x^4}


= 36(1)/(x^(4))((1)/(2^4))}x^4


= (36x^4)/(16x^4)


= (9)/(2)

User Jonthornham
by
5.5k points
2 votes

Answer:

2.25

Explanation:


(6x^(-2))^2(0.5x)^4\\ \\ =(6)^2\cdot(x^(-2))^2\cdot(0.5)^4\cdot(x)^4\\ \\=36\cdot x^(-4)\cdot 0.0625 \cdot x^4\\ \\= (36\cdot 0.0625)(x^4\cdot x^(-4))\\ \\=(2.25)(1)\\ \\=2.25

User Wienczny
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.